The Role of Business Risk and Non Debt Tax Shields to Debt to Equity Ratio on Pharmacy Listed Companies in Indonesia - Suratno, Suratno; Djaddan, Syahril; Ghozali, Imam (International Journal of Economics and Financial Issues, 2017)
The purpose of this study was to analyze the effect of interest earned time and business risk effect on debt to equity ratio and to determine the role of non-debt tax shields moderate the relationship between time interests earned and business risk on capital structure. There are 12 companies of pharmaceutical industries in Indonesia and the ones that meet the requirements are only 9 pharmaceutical industries. The data are analyzed and interpreted using the analysis tool of Struktur Equation Modeling with WarpPLS 5.0. Program is Variance or component based SEM is used to analyze hypotheses. The study concluded that Time Interest Earned and Interest Earned Time interaction with Tax Debt Non Shields no significant effect on Debt to Equity Ratio and to variable Business Risk and Business Risk Interactions with non-debt tax Shields significant effect on Debt to Equity Ratio. The results of this study are non-debt tax shields strengthen the relationship between the business risk of the debt to equity ratio which correspond to trade off theory, where the company made tax savings by using additional debt invested on fixed assets when the level of business risk is low and does not use additional debt when the company’s business is high-risk. Keywords: Debt to Equity Ratio, Time Interest Earned, Business Risk, Non Debt Tax Shields. JEL Classifications: G31, H25, H63